1995
DOI: 10.1152/ajpregu.1995.268.1.r192
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of NPY/NPY Y1 receptor/G protein system in rat brain cortex

Abstract: Neuropeptide Y (NPY) content, NPY receptors, and alpha-subunits of the G proteins Go and Gi were determined in cerebral cortex of male normotensive Wistar-Kyoto and spontaneously hypertensive rats at 3-28 wk of age and of adult female rats. NPY lacked major effects on adenylate cyclase or inositol phosphate formation. NPY content was similar in all normotensive groups but lower in spontaneously hypertensive rats at all ages. 125I-NPY labeled a homogeneous population of Y1-like receptors. The Y1 NPY receptor nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…In our own studies we have previously reported Gprotein alterations in erythrocytes and platelets of adult HD and CAPD patients [8], but their regulation may depend on cell type rather than mode of dialysis. This is in good agreement with a large body of data indicating that within a given animal regulation of G-protein expression by, e.g., thyroid hormone [15] or arterial hypertension [9,10], also occurs in a tissue-dependent manner. In the present study a similar platelet expression of 伪-subunits of G i2 , G i3 , G s long and G s short was observed in HD and control children.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our own studies we have previously reported Gprotein alterations in erythrocytes and platelets of adult HD and CAPD patients [8], but their regulation may depend on cell type rather than mode of dialysis. This is in good agreement with a large body of data indicating that within a given animal regulation of G-protein expression by, e.g., thyroid hormone [15] or arterial hypertension [9,10], also occurs in a tissue-dependent manner. In the present study a similar platelet expression of 伪-subunits of G i2 , G i3 , G s long and G s short was observed in HD and control children.…”
Section: Discussionsupporting
confidence: 91%
“…All analyses were performed as recently described [9,10]. Briefly, blood samples were obtained prior to hemodialysis after 2 days without dialysis.…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…Sex-related differences in receptor affinity, expression and signal transduction may be responsible. Although the present study did not address receptor affinity per se, it is interesting that Y 1 receptors in female rat cerebral cortex show a greater affinity for NPY than Y 1 receptors in male rat cerebral cortex (Michel et al 1995).…”
Section: Discussionmentioning
confidence: 82%
“…The complexity of sex-dependent differences in NPY-induced cardiovascular control is advanced by studies of cortical Y 1 R expression and sensitivity. Michel et al (75) examined the cerebral cortex of Wistar-Kyoto rats and SHR and noted that although the number of Y 1 R was similar between the breeds, females had half as many Y 1 R compared with males. However, binding affinity of these Y 1 R in females was twice that of males (75).…”
Section: Role Of Neuropeptide Y In the Regulation Of Vasomotor Tonementioning
confidence: 99%